Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

please give me the answer of the question given to the picture

please give me the answer of the question given to the picture

Question Image
Grade:10

1 Answers

Avishek Bhagat
askIITians Faculty 71 Points
8 months ago
Dear Student,
the solution to your query is:-

b2+c2-a2

=>(b+c)2–2bc-a2 [(b+c)2=b2+c+2bc]

=>(b+c+a)(b+c-a)-2bc[a2-b2=(a+b)(a-b)]

=>b2+c2-a2= -2bc[ a+b+c=0]

Similarly, we can prove

a2+c2-b2=-2ac
a2+b2-c2=-2ab

Putting the above values in given equation

=>1/2(-1/bc-1/ca-1/ab)

=>-1(a+b+c)/2abc[a+b+c=0]

=>0

askIITians Expert
Yuvraj Singh

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free